A comparison of trace element concentrations in surface and deep water of the Keban Dam Lake (Turkey) and associated health risk assessment - Canpolat, Ozgur; Varol, Memet; Okan, Ozlem Oztekin; Eris, Kursad Kadir; Caglar, Metin (Academic Press Inc Elsevier Science, 2020)
Keban Dam Lake (KDL) is the second largest dam lake in Turkey. There have been some reports on the trace element (TE) levels in surface water of the KDL, but its deep water has been never studied. We measured 17 TEs (Pb, Hg, Cd, As, Cr, Ni, Co, Mn, Cu, Fe, Al, Sr, U, V, Zn, Zr and Ba) in surface and deep water samples and assessed their health risks for residential and recreational receptors. Copper, Zn, Ba, Ni, Mn and Pb levels in deep water were higher than those in surface water. Total TE level in deep water was higher in wet season, whereas that in surface water was higher in dry season. TE levels in both surface and deep water were much lower than the guideline values for drinking water and the protection of freshwater aquatic life, indicating that TEs in the KDL originate from natural sources. All HQ (hazard quotient) and HI (hazard index) values were below the risk threshold of unity. HI values for child were higher than those for adult, indicating that the health of children is at dramatically higher risk than adults. Arsenic and U for water ingestion were the primary contributors to total risk (HI), while V and Cr for dermal pathway. The presence of U and V, among the TEs which are major contributors to total health risk, reveals the necessity of monitoring of such less-studied elements in the surface water bodies. Carcinogenic risk values of As and Cr in surface and deep water were below the target risk of 1 x 10(-4). These findings indicated that TEs in surface and deep water of the KDL do not pose health risks to residential and recreational users. Thus this study may serve as a model for similar studies assessing health risks of multielements in freshwater bodies in future.
Keywords: Trace elements; Dam lake; Surface and deep water; Risk assessment